2018
DOI: 10.4102/sajems.v21i1.1964
|View full text |Cite
|
Sign up to set email alerts
|

The effect of industry nuances on the relationship between corporate governance and financial performance: Evidence from South African listed companies

Abstract: Background: Premised on agency, resource dependence and stewardship theories, the study investigates empirically the existence of industry nuances in the relationship between corporate governance and financial performance of companies listed in the Johannesburg Stock Exchange. Aims: The main objective of the study is to understand the relationship between internal corporate governance and company performance from the perspective of three distinct economic periods, as well as industry nuances, cognisant of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…Although there has been an increasing interest in responsible corporate policies and practices in emerging markets, limited ESG research has been conducted in South Africa. Local researchers have mainly focused on corporate social responsibility (CSR) and corporate governance (Jordaan, De Klerk & De Villiers 2018;Mans-Kemp, Erasmus & Viviers 2017;Marcia, Maroun & Callaghan 2015;Tshipa et al 2018). The key motivation for firms to engage in CSR, however, is to improve society.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been an increasing interest in responsible corporate policies and practices in emerging markets, limited ESG research has been conducted in South Africa. Local researchers have mainly focused on corporate social responsibility (CSR) and corporate governance (Jordaan, De Klerk & De Villiers 2018;Mans-Kemp, Erasmus & Viviers 2017;Marcia, Maroun & Callaghan 2015;Tshipa et al 2018). The key motivation for firms to engage in CSR, however, is to improve society.…”
Section: Introductionmentioning
confidence: 99%
“…Li 2016;Orlitzky et al 2003;Roberts & Whited 2013) and the social disclosure patterns across different industries and the institutional micro-and macro-settings (e.g. Garcia-Sanchez et al 2016, Tshipa et al 2018, due to associated costs and benefits with diverse industry features. The SA context makes an interesting case to examine voluntary social disclosures, specifically due to its long history of racial segregation, termed apartheid, which resulted in many social disadvantages to the majority of the SA population (Southall 2004).…”
Section: Theoretical Background Prior Research and Hypothesesmentioning
confidence: 99%
“…De Klerk and De Villiers (2012), using a modified Ohlson model, found that corporate responsibility reporting is significantly positively related to market value. Horn, De Klerk and De Villiers (2018) using survey data by KPMG International on CSR contend that social disclosure has a positive but weak effect on future profits. The advent of socially responsible behaviour, linked to international standardisation, through sustainability reports, ultimately seeks to ensure the long-term sustainability and survival of organisations, while maximising shareholder value and FP.…”
Section: Theoretical Background Prior Research and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations